2005
DOI: 10.1038/sj.npp.1300705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Altered Amygdalar Neuropeptide Y Expression on Anxiety-Related Behaviors

Abstract: Neuropeptide Y (NPY) decreases anxiety-related behaviors in various animal models of anxiety. The purpose of the present study was to examine the role of the amygdalar NPY system in anxiety-related responses in the elevated plus maze. The first experiment determined if herpes virus-mediated alterations in amygdalar NPY levels would alter anxiety-related behaviors in the elevated plus maze. Viral vectors encoding NPY, NPY antisense, or LacZ (control virus) were bilaterally injected into the amygdala, and 4 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 59 publications
8
64
1
1
Order By: Relevance
“…NPY levels in the amygdala (by injecting viral vector encoding NPY), as compared to rats with downregulated NPY release (by injecting NPY antisense) (Primeaux et al, 2005). Hence, it is likely that attenuated neuronal activation in the amygdala observed in the present study is crucially implicated in the anxiolytic phenotype of Y2 −/− mice.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 63%
“…NPY levels in the amygdala (by injecting viral vector encoding NPY), as compared to rats with downregulated NPY release (by injecting NPY antisense) (Primeaux et al, 2005). Hence, it is likely that attenuated neuronal activation in the amygdala observed in the present study is crucially implicated in the anxiolytic phenotype of Y2 −/− mice.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 63%
“…The specific Y1 antagonist BIBO3304 blocks the anxiolyticlike effect of NPY administrated into amygdala in the social interaction test (Sajdyk et al, 1999). In addition, a recent study demonstrated that overexpression of NPY in the amygdala of rats reduced anxiety-like behaviors through Y1 receptor (Primeaux et al, 2005). Taken together, these studies suggest that anxiolytic-like effects of NPY are mediated via Y1 receptors.…”
Section: Introductonmentioning
confidence: 85%
“…The release of NPY is thought to facilitate the containment of negative consequences following exposure to stress and has anxiolytic-like effects (Heilig, 2004). Intracerebroventricular administration of NPY or NPY-Y1-receptor agonists decrease anxiety-related behaviors in the Geller-Seifter conflict test, fear potentiated startle test, and the elevated plus maze (EPM) test, without altering locomotor activity (Britton et al, 1997(Britton et al, , 2000Broqua et al, 1995;Heilig et al, 1989;Primeaux et al, 2005). Intracerebroventricular administration of antisense oligonucleotides for the NPY-Y1 receptor or the non-peptide NPY-Y1-receptor antagonist (Y1RA), BIBP3226, increases anxiety-related behaviors in the EPM test (Kask et al, 1996;Wahlestedt et al, 1993).…”
Section: Introductonmentioning
confidence: 99%
“…32 In agreement, NPY knockout mice demonstrate anxiogenic responses in the open field, elevated plus maze and light-dark tasks, 33,34 while viral vectorinduced overexpression of NPY in the amygdala leads to attenuated anxiety on the elevated plus maze. 35 There is general consensus that anti-anxiety actions of NPY are primarily mediated by the Y1 receptor subtype in the amygdala, 36 although other regions such as the bed nucleus of stria terminalis may also contribute towards anti-anxiety effects. 37 Y1-selective antagonists, BIBO3304 and BIBP3226, block anxiolytic effects of NPY in the several paradigms.…”
Section: Npy: Anxietymentioning
confidence: 99%